Impact of Mental Health and Stress on Academic Performance among Students: A Literature Review - Musfirah, Musfirah; Burhan, Imron; Hatibu, Hardiyanti; Ridhoh, M. Yunasri; Marsuki, Andika (Journal of Education Method and Learning Strategy, 2025)
This article discusses the impact of mental health and academic stress on students' academic performance through a literature review. The objective of this study is to identify how mental well-being and stress levels affect learning effectiveness and academic achievement. The method employed is a literature analysis of various studies that explore the relationship between mental health, academic stress, and learning outcomes. The findings indicate that stable mental health contributes positively to increased focus, motivation, and comprehension of learning materials. Conversely, unmanaged stress can impair concentration, reduce interest in learning, and negatively affect academic results. However, in certain cases, academic stress (when experienced at optimal levels, or eustress) can serve as a motivating factor that enhances academic performance. Factors such as the learning environment, social support, and teaching methods also play a role in moderating the impact of mental conditions on student achievement. Therefore, it is essential for educational institutions to provide mental health intervention programs, counseling services, and adaptive learning approaches to help students manage stress and improve their academic performance.